Herbicide-resistant crops in resistant weed management : An industrial perspective - Shaner, D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Some of the first products of biotechnology to reach the marketplace have been herbicide-resistant crops. Industry sees the development of herbicide-resistant varieties as a way to increase the availability of proven herbicides for a broader range of crops. However, the development of herbicide- resistant crops requires special attention to potential environmental questions such as herbicide usage, selection of resistant weed biotypes and spread of resistance from the resistant crop to wild species. Industry is actively addressing these concerns during the process of development. Proper development and use of herbicide-resistant crops in integrated weed management programs will provide farmers with increased flexibility, efficiency, and decreased cost in their weed control practices without increasing the risk of herbicide-resistant weeds. Furthermore, herbicide-resistant crops should prove to be valuable tools in managing herbicide- resistant weeds.